Effect of Adolescent Pregnancy on Dental Caries Experience and Selected Salivary Physicochemical Characteristics - Aljabari, Balsam A.; Hoobi, Nibal M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Adolescent pregnancy is associated with major health consequences for adolescent pregnant women, including medications and oral health problems such as dental caries and periodontal disease. Pregnancy is a unique state of physical, hormonal, and metabolic changes that can result in an oral cavity imbalance. Changes in salivary components and a decrease in salivary flow rate caused by an increase in progesterone may compromise saliva’s protective effects, resulting in dental caries. Objectives: To evaluate dental caries experience in adolescent pregnancy. Method: A sample including 80 pregnant ladies was recruited in this study and categorized into a study group involving 40 primigravida adolescent females aged 15-19 years old and a control group involving 40 primigravida women (20-32) years old who married at age 20 years or more, all of them in the second trimester of pregnancy. Unstimulated salivary samples were collected, and salivary flow rate, pH, and dental caries experience were assessed. Saliva samples were analyzed to estimate salivary lactoferrin concentration. Results: The mean (±sd) of decayed surfaces of the study group was (11.850±0.669) compared to (9.425±1.015) of the control group, and the level of salivary lactoferrin of the study group was (8.071±0.558) compared to (6.610±0.447) of the control group, while the mean (±sd) of a salivary flow rate of the study group was (0.349±0.020) compared to (0.540±0.157) of the control group and the mean (±sd) salivary pH was (5.935±0.053) compared to (5.995±0.153) of the control group. Conclusion: Adolescent pregnancy is linked to increased dental caries experience by altering salivary characteristics, including lactoferrin levels.